Bioremediation of plastics by the help of microbial tool: A way for control of plastic pollution - P. Lokesh; R. Shobika; SoghraNashath Omer; Madhavi Reddy; Panchamoorthy Saravanan; R. Rajeshkannan; V. Saravanan; S. Venkatkumar (Sustainable Chemistry for the Environment, 2023)
Plastics are a synthetic or semisynthetic material that is extensively used in our routine life because of its remarkable characteristics such as thermal, mechanical properties, durability, and stability, so they have widespread application. This massive use of plastics has caused various issues to human health and the environment. Nearly 700 species, including endangered species,have been affected by plastics. Enzyme - mediated and microbial degradation of plastic waste is a potential technique in which the process of biodeterioration, thermal decomposition, and integration actually took place and is ultimately transformed into gases and a microbial community, where the process leaves few residual effects. Recent studies have shown that bacteria and bacterial consortia, biofilm formation and fungi may biodegrade many polymers. Depending on the organisms, the molecular weight of the plastics, the kind of polymer, and the climate, waste plastic can be converted into methane, CO2, biomass, water and inorganic chemicals. Plastics induce oxidative stress, enhanced and inflammatory reactions, translocation or absorption, in people, animals and plants. Numerous studies have shown that people are susceptible to metabolic disorders, neurodegeneration, and malignancy.We have also talked about how we are working on using the metabolic processes of bacteria to minimize soil and water pollution by microplastics. More study is required to discover the crucial ecological characteristics and elements that affect plastic degradation in order to predict the fate of plastics in various contexts and to enable the development of solutions for minimising plastic waste.